The experimental study of the kinetics and modes of polymethyl methacrylate thermal degradation in argon flows; Thermochimica Acta; Vol. 736 - Salgansky E. A. Evgeny Aleksandrovich; Salganskaya M. V.; Glushkov D. O. Dmitry Olegovich; Pleshko Andrey Olegovich A. O. (2024, 2024)
Title screen